2010
DOI: 10.1161/strokeaha.109.568790
|View full text |Cite
|
Sign up to set email alerts
|

Recanalization of Vertebral Artery Dissection

Abstract: Background and Purpose-We investigated the predictors and time course for recanalization after vertebral artery dissection. Methods-We prospectively studied 61 consecutive patients with confirmed diagnoses of vertebral artery dissection without intracerebral hemorrhage. Neuroimaging and clinical follow-up were performed at presentation and at 3, 6, and 12 months. Results-We included 61 patients with confirmed vertebral artery dissection; 19 were evaluated and followed up with conventional angiography, 24 with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
41
2
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 20 publications
3
41
2
2
Order By: Relevance
“…Case series comment that recanalization often occurs within the first 6 months or earlier, 1,215,220 that 82% of healing occurs within the first year with a median time to healing of 3 to 4 months, 8 and that median time until near or total recanalization was 4.7 months. 2 Again, no reports commented on any association with CMT.…”
Section: Follow-up Of Dissected Arteriesmentioning
confidence: 99%
See 1 more Smart Citation
“…Case series comment that recanalization often occurs within the first 6 months or earlier, 1,215,220 that 82% of healing occurs within the first year with a median time to healing of 3 to 4 months, 8 and that median time until near or total recanalization was 4.7 months. 2 Again, no reports commented on any association with CMT.…”
Section: Follow-up Of Dissected Arteriesmentioning
confidence: 99%
“…In general, the majority of patients with strokes caused by CDs have good outcomes, with rates that vary from 70% to 92%. 8,59,98,160,[215][216][217][218][219][220] Even a small series of 12 cases with 3 or 4 simultaneous dissections on initial diagnosis from 3 European centers showed excellent outcomes (mRS score=0-1) in 83%. 221 Associations with better outcomes include ICAD that had shown recanalization 215 and lesser initial stroke severity.…”
mentioning
confidence: 99%
“…The mean age of our patients was younger (55.8 years) than in most series (≥60 years-old); this is probably the result of a referral bias to a tertiary-level stroke facility, with higher frequency of spontaneous cerebral vessel dissections [30,31], cardiac valvular lesions from rheumatic fever, CVTs, and other infrequent pathologies. Also, a high frequency (59%) of left-sided ischemic lesions increases VaD risk 5-fold (OR 5.0; 95% CI 1.92-14.1) [32].…”
Section: Discussionmentioning
confidence: 78%
“…Similarly, we arbitrarily chose to consider patients with unchanged VA occlusion as non-VAD patients. A longer monitoring period might have shown late recanalization, though Arauz et al 24 recently demonstrated that recanalization of VAD occurs mainly within the first 6 months after the onset of symptoms, even in the case of occlusion. Finally, in the case of multiple VADs (2 patients), we chose to consider only the symptomatic VAD, given that the treatment does not depend on the number of dissected vessels, and to avoid an artificial increase in the population.…”
Section: Discussionmentioning
confidence: 99%